THE COMBINED EFFECT OF MOISTURE AND TEMPERATURE ON THE ANOMALOUS EXPANSION BEHAVIOUR OF MARBLE - Koch A.; Siegesmund S. (My University, 2004)
Three calcitic marble types often used as cladding material and different in lattice preferred orientation (texture), grain shape preferred orientation, grain size distribution and grain interlocking are investigated to study the combined effect of thermal cycles (day-night) and moisture on the decay of marble, particularly on the bowing phenomenon. Repetitive heating-cooling under dry conditions leads to considerable inelastic residual strain only in the first thermal cycle. The residual strain continuously increases again if water is present, whereby the moisture content after a thermal cycle has a certain impact on the decay rate. The water-enhanced thermal dilatation strongly correlates with the deterioration rate obtained from the laboratory bow test. All applied approaches reveal that the texture in combination with the grain shape preferred orientation control the intensity and anisotropy of marble deterioration, thus, the cutting direction of facade panels has to be considered in terms of durability. On-site analysis from building facades confirm the laboratory results such as the bowing tendency of different marbles, directional dependence, relevance of moisture content during cyclical heating and the loss of strength due to environmental impact.